The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1002/j.1460-2075.1992.tb05375.x
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus E6 proteins bind p53 in vivo and abrogate p53-mediated repression of transcription.

Abstract: The transforming proteins of DNA tumor viruses SV40, adenovirus and human papillomaviruses (HPV) bind the retinoblastoma and p53 cell cycle regulatory proteins. While the binding of SV40 large T antigen and the adenovirus E1B 55 kDa protein results in the stabilization of the p53 protein, the binding of HPV16 and 18 E6 results in enhanced degradation in vitro. To explore the effect of viral proteins on p53 stability in vivo, we have examined cell lines immortalized in tissue culture by HPV18 E6 and E7 or SV40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
3
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(175 citation statements)
references
References 65 publications
16
152
3
4
Order By: Relevance
“…For instance the product of the mdm2 oncogene, which binds and is believed to mask the activation domain of p53, is overexpressed in certain tumours, resulting in the abrogation of p53 function, accompanied by the proteolytic degradation of p53, mediated by the ubiquitin pathway Oliner et al, 1992Oliner et al, , 1993Midgley and Lane, 1997). Additional data showed that p53 may down-regulate the expression from a number of other promoters including those of the c-fos, c-jun, c-myc, b-actin, hsc-70, IL-6 genes (Ginsberg et al, 1991;Lechner et al, 1992;Ko and Prives, 1996). In contrast to the p53-mediated transactivation, the p53-mediated transrepression does not involve an interaction between p53 and DNA.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…For instance the product of the mdm2 oncogene, which binds and is believed to mask the activation domain of p53, is overexpressed in certain tumours, resulting in the abrogation of p53 function, accompanied by the proteolytic degradation of p53, mediated by the ubiquitin pathway Oliner et al, 1992Oliner et al, , 1993Midgley and Lane, 1997). Additional data showed that p53 may down-regulate the expression from a number of other promoters including those of the c-fos, c-jun, c-myc, b-actin, hsc-70, IL-6 genes (Ginsberg et al, 1991;Lechner et al, 1992;Ko and Prives, 1996). In contrast to the p53-mediated transactivation, the p53-mediated transrepression does not involve an interaction between p53 and DNA.…”
Section: P53 a Sequence Speci®c Transactivatormentioning
confidence: 99%
“…Extracts were normalized for protein concentration and assayed for CAT enzyme activity (Ludes-Meyers et al, 1996). Because wild-type p53 inhibits and mutant p53 activates di erent promoters to varying extents Ginsberg et al, 1991;Lechner et al, 1992;Santhanam et al, 1991;Subler et al, 1992), it was not possible to use an internal control such as pSVbGal or RSVbGal (Ludes-Meyers et al, 1996). A similar situation has been recognized for SV40 T antigen-mediated regulation of promoters (Gruda et al, 1993).…”
Section: Chloramphenicol Acetyltransferase Assaymentioning
confidence: 99%
“…Deletion of the first element, the E1B 55 kDa fragment, enables replication of Onyx 015 in cells with a defective p53 pathway (cancer cells) 2,46,47 and minimizes replication in cells with a functional p53 pathway (normal cells). Some controversy exists on whether or not the sole mechanism by which Onyx 015 has selective replication capacity in malignant cells is related to p53.…”
Section: Onyx 015mentioning
confidence: 99%